BANK SAMPAH SOLUSI MENGURANGI SAMPAH RUMAH TANGGA (Studi Kasus Bank Sampah Puri Pamulang) - Masruroh Masruroh (Masyarakat Madani: Jurnal Kajian Islam dan Pengembangan Masyarakat, 2021)
This research was conducted to see how far the waste bank in the Puri Pamulang housing complex has been a solution in reducing household waste. The results of this study are based on the results of interviews with the household waste community before the existence of a mind set waste bank, the waste produced was only burned, disposed of in trash cans or taken by scavengers who came to the Puri Pamulang area. The Garbage Bank activity in Puri Pamulang is the collection of dry waste that has been sorted with good management so that bank customers are like saving in a bank by saving waste. Counseling for residents is also carried out through waste bank socialization activities, training involving waste bank members/managers, and involvement of the waste bank community in the South Tangerang area under the auspices of the DLH. The supporting factors in managing the Waste Bank in Puri Pamulang are: Member involvement, infrastructure, community involvement and collaboration with the South Tangerang Environmental Service.